Clusterin inhibits Aβ42 aggregation through a "strawberry model" as detected by FRET‐FCS. Issue 2 (29th March 2021) - Xu, Lingwan; Tian, Shijun; Peng, Xianglei; Hua, Ying; Yang, Wenxuan; Chen, Longwei; Liu, Shilei; Wu, Wenzheng; Zhao, Jiang; He, Jinsheng; Wu, Liqing; Yang, Jingfa; et al.
Abstract: Extracellular plaque deposits of β‐amyloid peptide (Aβ) are one of the main pathological features of Alzheimer's disease (AD). The aggregation of Aβ42 species, especially Aβ42 oligomers, is still an active research field in AD pathogenesis. Secretory clusterin protein (sCLU), an extracellular chaperone, plays an important role in AD pathogenesis. Although sCLU interacts directly with Aβ42 in vitro and in vivo, the mechanism is not clear. In this paper, His‐tagged sCLU (sCLU‐His) was cloned, expressed and purified, and we applied florescence resonance energy transfer‐fluorescence correlation spectroscopy (FRET‐FCS) to investigate the direct interaction of sCLU‐His and Aβ42 at the single‐molecule fluorescence level in vitro. Here, we chose four different fluorescently labeled Aβ42 oligomers to form two different groups of aggregation models, easy or difficult to aggregate. The results showed that sCLU‐His could form complexes with both aggregation models, and sCLU‐His inhibited the aggregation of Aβ42/RB Aβ42/Atto647 (easy to aggregate model). The complexes were produced as the Aβ42/Label adhered to the sCLU‐His, which is similar to a "strawberry model, " as strawberry seeds are dotted on the outer surface of strawberries. This work provided additional insight into the interaction mechanism of sCLU and Aβ42 . Abstract : We applied fluorescence resonance energytransfer‐fluorescence correlation spectroscopy (FRET‐FCS) to investigate the direct interaction of sCLU‐His and amyloid beta Aβ42 at the single‐molecule fluorescence level in vitro. The results showed that His‐tagged secretory clusterin protein histamin (sCLU ‐His) could form complexes with Aβ42/Label and inhibited the aggregation of Aβ42/Label . Furthermore, the inhabitation mechanism was that the Aβ42/Label adhered to sCLU‐His, just like strawberry seeds are dotted on the outer surface of strawberries. We call this mechanism "strawberry model" and we think this hypothesis provides additional insight into the interaction of sCLU‐His and Aβ42 .